World Economy Autumn 2020 - Gradual recovery after partial rebound - Klaus-Jürgen Gern; Philipp Hauber; Stefan Kooths; Ulrich Stolzenburg (Kiel Institute for the World Economy (IfW), 2020)
The world economy contracted by close to 10 percent in the first half of 2020 as the COVID-10 pandemic unfolded. After a 3 percent drop in activity in the first quarter, global output contacted by some 7 percent as governments around the world implemented measures to contain the virus and households voluntarily adopted social distancing and reduced spending in certain activities to avoid getting infected. Since then, output is recovering. While we generally expect a strong rebound in in the short term, pre-crisis levels of GDP will be approached only towards the end of the forecast horizon in many countries. Further normalization of economic activity is likely to be gradual as long as the pandemic is lingering and inhibiting activity in important sectors of the economy. Global output measured at PPP exchange rates will shrink by 3.6 percent this year. For 2021 we expect a rebound with growth of 6.7 percent. This represents an upward revision of our June forecast by 0.2 and 0.5 Percentage points, respectively. In 2022, we expect GDP to increase by 4.1 percent. However, a deterioration of longer-term business prospects in the wake of lower incomes and weaker balance sheets of firms around the globe are likely to weigh on investment. As a result, we do not expect world output to return to the pre-crisis trend in the coming years.
Keywords: 330; advanced economies; emerging economies; monetary policy; COVID19